With hope and disapointment: the first duma in the socio-political journalism of Mykhailo Hrushevsky - Колесник, Віктор; Чеберяко, Оксана (ВПЦ "Київський університет", 2025)
Background. The journalistic works of Mykhailo Hrushevsky are analyzed, which reflect the author's perception and understanding of the elections to the First Duma, the Ukrainian Parliamentary Club, reveal certain features of the autonomist faction, the reasons for the dissolution of the First Duma, the results and significance of its activities. Methods. The method of historiographic analysis of socio-political journalism based on the principles of historicism and objectivity is applied. Results. Mykhailo Hrushevskyi's journalistic analysis shows that the author made his contribution to the historiographic understanding of the First Duma. In particular, he recognized the imperfection of the electoral legislation (curial election system), which limited the opportunities for the Ukrainian masses, identified the peculiarities of the election campaign in Ukraine, carried out an analysis and assessment of the deputy corps of the First Duma, the Ukrainian representation in it. In journalism from the angle of Ukrainian interests, the creation of the Ukrainian parliamentary club in the First Duma is considered, the peculiarities of the composition of the autonomist faction are determined, the position of deputies who allowed the division of nationalities into "mature" and "immature" is criticized, the author's perception of its activity, dissolution and meaning is presented. ConclusIons. The socio-political journalism of Mykhailo Hrushevsky became an important component of the first period of the historiography of the First State Duma. The author's articles and materials, from the angle of Ukrainian national-political interests, consider important aspects related to the electoral process, the deputy composition of the Duma, the Ukrainian Parliamentary Club, and the autonomist faction. A general assessment of its activities and significance is formed.

Вступ. Проаналізовано публіцистичні праці Михайла Грушевського, у яких відображено авторське сприйняття й осмислення виборів до І Думи, Українського парламентського клубу, розкриті певні особливості фракції автономістів, причини розпуску І Думи, результати і значення її діяльності. Методи. Застосовано методи аналізу, систематизації та узагальнення суспільно-політичної публіцистики на основі принципів історизму й об'єктивності. Результати. Аналіз публіцистики Михайла Грушевського свідчить, що вчений зробив свій вагомий внесок в історіографічне осмислення  І Думи. Зокрема, він визнав  недосконалість виборчого законодавства (куріальна система виборів), що обмежувало можливості для українських народних мас, визначив особливості виборчої кампанії в Україні, здійснив  аналіз й оцінку депутатського корпусу І Думи,  українського представництва в ній. У публіцистиці під кутом українських інтересів розглянуто створення українського парламентського клубу в І Думі, визначено особливості складу фракції автономістів, піддано критиці позицію депутатів, які  допускали поділ народностей на "зрілі" й "незрілі", подано авторське сприйняття її діяльності, розпуску та значення.   Висновки.  Суспільно-політична публіцистика Михайла Грушевського стала важливою складовою першого періоду історіографії І Держаної думи. В авторських статтях і матеріалах  під кутом українських національно-політичних інтересів розглянуто важливі аспекти, пов'язані з виборчим процесом, депутатським складом Думи, Українським  парламентським клубом, фракцією автономістів. Сформовано загальну оцінку її діяльності та значення.
З надією і розчаруванням: І Дума в суспільно-політичній публіцистиці Михайла Грушевського
Keywords: публіцистика; Михайло Грушевський; історіографія; І Дума; Україна; journalism; Duma; Mykhailo Hrushevsky; Ukraine; historiography